Understanding CRY2 interactions for optical control of intracellular signaling - Liting Duan (Nature Portfolio, 2017)
Cryptochrome 2 (CRY2) can form light-regulated CRY2-CRY2 homo-oligomers or CRY2-CIB1 hetero-dimers, but modulating these interactions is difficult owing to the lack of interaction mechanism. Here the authors identify the interactions facilitating homo-oligomers and introduce mutations to create low and high oligomerization versions.